Conceptual Design of an On-Axis 6 m Space Telescope at the Diffraction Limit: Characteristics, Performance and Advantages - Ariadna Calcines Rosario (Aerospace, 2023)
This paper presents the conceptual design of an on-axis 6 metre aperture space telescope designed to cover a field of view of ±0.2 degrees with an optical quality at the diffraction limit within a spectral range between 0.5 μm and 2.5 μm. The plate scale is 3 arcsec/mm, and the overall length is less than 12 m. A Korsch layout has been selected based on the superb aberration compensation offered by Three-Mirror Anastigmat systems. The proposed design presents some characteristics: an almost flat response in RMS wavefront error across the field and for the entire spectral range; a flat mirror has been included to reduce the overall volume, and this has been adjusted to be placed at an intermediate pupil position, acting as a baffle for stray light and as a Lyott to restrict background radiation. This mirror presents a central hole, defined to the aperture of the pupil, allowing the transmission of the beam towards the image focal plane, where it can be split for multiple payloads. It also allows the transmission of the central field, at 90 degrees with respect to the science beam, to be used for Active Optics monitoring and correction of the primary mirror in order to ensure optimum optical performance. This on-axis solution significantly reduces the technical complexity for manufacturing, metrology, integration, and tests and has an important impact in the cost of the telescope.